+0  
 
0
138
1
avatar+2509 

Help.

NotSoSmart  Jan 4, 2018
 #1
avatar+87334 
+1

-x^2  + 5x  =  3       rearrange as

 

x^2  - 5x  +  3   =  0

 

a  = 1    b  = -5    c  = 3

 

So....the solutions are

 

-(-5) ± √  [  (-5)^2  -  4(1)(3)  ]

_______________________

           2(1)

 

 

5  ± √[ 25  -  12  ]

______________

           2

 

5/2   ± √13/2

 

 

 

(-5i)(-3i)  =

 

15i^2  =

 

15(-1)  =

 

-15

 

 

cool cool cool

CPhill  Jan 4, 2018

7 Online Users

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.